The experience of internal and external supporting objects from the perspective of six young women who have lost a parent to cancer- An interpretative phenomenological analysis - Nilsson D; Johansson E; Larsson K; Näslund J (Annals of Psychiatry and Treatment - Peertechz Publications, 2017)
Background: Adolescents losing a parent are a risk group for future complications in their ongoing live such as higher rate of mortality, self- harm and other mental health problems. There is a lack of knowledge in what, how and when to offer help as well as no concluding theoretical model to understand the whole process of losing a parent. The objective of this study was to examine how the relationships of some young people are affected by the loss of a parent to cancer during their teenage years. Method: Six women aged between 18 and 25 participated in the study. An Interpretative Phenomenological Analysis (IPA) method was used. Result: The theme of loneliness was cemented with the two main themes, into loneliness and out of loneliness and sub-themes such as, cancer comes along, silence, hold on to and miss, those closest, the supporters, independence, closeness and distance. Conclusion: The parent who has died lives on as an inner object and the support from the remaining parent is viewed very important. The process to be back on track seems diverse and continues for a long time and outside help needs to tune in with this.